2011
DOI: 10.3390/e13020554
|View full text |Cite
|
Sign up to set email alerts
|

Amines in the Earth’s Atmosphere: A Density Functional Theory Study of the Thermochemistry of Pre-Nucleation Clusters

Abstract: The impact of organic species which are present in the Earth's atmosphere on the burst of new particles is critically important for the understanding of the molecular nature of atmospheric nucleation phenomena. Amines have recently been proposed as possible stabilizers of binary pre-nucleation clusters. In order to advance the understanding of atmospheric nucleation phenomena, a quantum-chemical study of hydrogen-bonded complexes of binary sulfuric acid-water clusters with methyl-, dimethyl-and trimethylamines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
175
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(194 citation statements)
references
References 59 publications
(106 reference statements)
17
175
2
Order By: Relevance
“…Both Nadykto et al [1] and our study [2] agree that the binding of most amines to a single sulfuric acid molecule is considerably stronger than that of ammonia. Primary and secondary amines also promote the addition of a second sulfuric acid to the cluster more effectively than ammonia, though the two studies disagree in the magnitude of the difference.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Both Nadykto et al [1] and our study [2] agree that the binding of most amines to a single sulfuric acid molecule is considerably stronger than that of ammonia. Primary and secondary amines also promote the addition of a second sulfuric acid to the cluster more effectively than ammonia, though the two studies disagree in the magnitude of the difference.…”
Section: Introductionsupporting
confidence: 86%
“…This comment is intended to address some issues related to that discussion. Specifically, it is shown that the errors related to basis-set effects in our calculations are very likely much smaller than claimed by Nadykto et al [1]. Composite calculations including e.g., higher-level electron correlation also agree better with our results.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The importance of amines for NPF has recently been established by field (Angelino et al, 2001;Makela et al, 2001;Smith et al, 2010;Zhao et al, 2011) and laboratory experiments (Murphy et al, 2007;Berndt et al, 2010;Erupe et al, 2011;Bzdek et al, 2010;Zhao et al, 2011;Yu et al, 2012;Zollner et al, 2012;Almeida et al, 2013;Jen et al, 2014;Kurten et al, 2014), as well as from modelling studies (Kurten et al, 2008;Barsanti et al, 2009;Bzdek et al, 2010;Ortega et al, 2012;Loukonen et al, 2010;Nadykto et al, 2011;Paasonen et al, 2012;Almeida et al, 2013;DePalma et al, 2014). On a molecular level, Kurten et al (2014) observed how DMA stabilises SA, increasing the stable cluster concentration by up to 6 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%